Phylogenetic relationships and characterization of the complete chloroplast genome of strawberry, Fragaria x ananassa (Rosaceae: Fragaria). Issue 1 (2nd January 2019) - Huang, Jing; Zhao, Xiaoxu; Lin, Suying; Wang, Xiumei; Zhou, Fengchao; Huang, Jianhui
Abstract: Strawberry ( Fragaria x ananassa ) is an economically and important fruit species that is grown extensively around the entire world. In this study, we obtained the complete chloroplast genome of F. x ananassa . The chloroplast genome of F. x ananassa is 155, 529 bp in size, containing a large single-copy region (85, 523 bp), a small single-copy region (18, 136 bp) and a pair of IR regions (each one of 25, 935 bp). The overall GC contents of the chloroplast genome is 37.2%. The chloroplast genome of F. x ananassa contains 135 genes, including 90 protein-coding genes, 37 tRNA genes, and eight rRNA genes. The phylogenetic maximum-likelihood (ML) tree was constructed and based on 18 species plants and F. x ananassa chloroplast genomes, which F. x ananassa is closest related to Fragaria vesca subsp. vesca in phylogenetic relationship. This complete chloroplast genome can be further used for genomic studies, phylogenetic analyses, and genetic engineering studies of the genus Fragaria.